The effect of work environment and organizational culture on employee performance mediated by work motivation (Study on operational field employee of PT. Bank Pembangunan Daerah Provinsi Jawa Timur Tbk) - Rachmat, Adiwiratna Briandana Ganefanto; Noermijati, Noermijati; Sudjatno, Sudjatno (MEC-J (Management and Economics Journal), 2019)
This research aims to examine and analyze the effect of the work environment and organizational culture on the operational field employee performance of PT Bank Pembangunan Daerah Provinsi Jawa Timur Tbk Cabang Sidoarjo with mediated work motivation. The population in this research was 134 employees. Data analysis in this research is the SEM using sofware PLS. The results of this research show that influential work environment significantly on the employee performance, organizational culture affect significantly on the employee performance, work environment affect significantly on the work motivation, organizational culture affect significantly on the work motivation, work motivation affect significantly on the employee performance. Motivation work also roles as a partial mediation from the effect of work environment on performance of employees and the effect of organizational culture on performance of employees.